2015
DOI: 10.1016/j.cmi.2014.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Mycobacterium tuberculosis isolates from foreign-born and Japan-born residents in Tokyo

Abstract: Sequences of the full genomes of 259 clinical isolates of Mycobacterium tuberculosis, obtained from foreign-born and Japan-born patients in Tokyo, Japan, were determined, and a phylogenetic tree constructed by concatenated single-nucleotide polymorphism (SNP) sequences. The 259 isolates were clustered into four clades: Lineage 2 (East Asian or "Beijing" genotype; n = 182, 70.3%), Lineage 4 (Euro-American, n = 46, 17.8%), Lineage 1 (Indo-Oceanic, n = 23, 8.9%), and Lineage 3 (East African-Indian, n = 8, 3.1%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Kobayashi et al . reported that in Tokyo, the proportion of lineage 1 isolates was significantly higher in foreign-born patients than in Japanese patients 26 . Therefore, a greater prevalence of lineage 1 isolates would be expected from foreign-born patients.…”
Section: Discussionmentioning
confidence: 91%
“…Kobayashi et al . reported that in Tokyo, the proportion of lineage 1 isolates was significantly higher in foreign-born patients than in Japanese patients 26 . Therefore, a greater prevalence of lineage 1 isolates would be expected from foreign-born patients.…”
Section: Discussionmentioning
confidence: 91%
“…This hypothesis, together with the high prevalence of L2.1 in Guangxi, conforms to the hypothesis that the origin of the Lineage 2, L2.1 and probably L2.2 or the Beijing strains was in Southern China 7 , where L2.2.2 or the RD181-positive Beijing strains were also highly prevalent 12 . The early L2.2 or Ancestral Beijing strains spread widely from Tibet 13 to Japan 14,15 . In south Eastern Asia they may have diversified by co-evolving with various genetically diverse non-Han Chinese ethnic tribes in the segregated mountainous areas.…”
Section: Discussionmentioning
confidence: 99%
“…To understand their spreading potential, the geographical origin of L2 or the Beijing strains are sought and debated. A number of studies suggested that they started in Southern China 7,12 and subsequently spread throughout Eastern Asia, from Tibet 13 to Japan 14,15 . The Modern Beijing strains appeared to successfully co-expand with Han Chinese in Northern China 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TB isolates from foreign-born patients may increase TB genetic diversity in Tochigi Prefecture. Although no direct evidence has shown that these isolates from foreign-born patients in Tochigi are a risk factor for TB transmission, similar findings were reported for TB isolates from foreign-born and Japan-born TB patients in Tokyo [3]. Of the 13 isolates belonging to Lineage 1, nine were from patients born in other Asian countries, including seven from Southeast Asian countries/regions, where Lineage 1 is predominant [6, 24].…”
Section: Discussionmentioning
confidence: 63%